Asset Integration and Attitudes toward Risk: Theory and Evidence - Andersen, Steffen; Cox, James C.; Harrison, Glenn W.; Lau, Morten I.; Rutström, E. Elisabet; Sadiraj, Vjollca (The Review of Economics and Statistics, 2018)
We provide evidence that choices over small-stakes bets are consistent with assumptions of some payoff calibration paradoxes. We then exploit the existence of detailed information on individual wealth of our experimental subjects in Denmark and directly estimate risk attitudes and the degree of asset integration. We discover that behavior is consistent with partial, rather than full, asset integration. The implied risk attitudes from estimating these specifications indicate risk premiums and certainty equivalents that are a priori plausible. This theory and evidence suggest one constructive solution to payoff calibration paradoxes.